Offering routine antenatal testing for HIV and hepatitis B in the rural setting of Cornwall. Issue 2 (1st April 2002) - Keane, F E A; Neale, J; Phillips, T; Heard, L; Jones, R; Guttridge, B; Bendall, R
Abstract : Before Department of Health directives to offer HIV and hepatitis B (HBV) testing to all pregnant women, there was little such screening in Cornwall. Through a multiagency collaborative approach a new antenatal screening programme for HIV/HBV has been introduced with high uptake in the first year (HIV 92% and HBV 93%). We also report the findings of a questionnaire survey of community midwives who alone offer antenatal HIV/HBV testing in Cornwall.